Effect of disparities of feedback on pacing in cycle time trials - Nyberg, K.; Jaime, S.; Rodriguez-Marroyo, J.; Condello, G.; Casolino, E.; Dodge, C.; Mikat, R.; Wright, G.; Foster, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The purpose of this study is to understand the effect of hypoxia during warm-up and competition on performance during cycle time trials. If the pre-exercise warm-up is manipulated by the use of hypoxia, when does the hypoxic challenge influence pacing during the time trial, performed under either normoxic or hypoxic conditions? Methods: Seven well-trained subjects performed a VO2 max test, two habituation trials, and four randomly ordered, single-blind 5 km time trials. Subjects performed HH (hypoxic WU/hypoxic TT), HN (hypoxic WU/normoxic TT), NH (normoxic WU/hypoxic TT), or NN (normoxic WU/hypoxic TT) with hypoxia (FiO2 =0.15) and normoxia (FiO2=0 .21). Results: The hypoxic warm-up elicited a significant (p < .05) decrease in arterial saturation (hypoxic SaO2=86%, normoxic SaO2=97%) and increases in perceived exertion (RPE) and blood lactate (HLA). During the time trial significant differences in PO between hypoxic and normoxic time trials began at 1.0 km, continuing for the duration of the time trial (NN PO @ 1,2,3,4,5 km=271, 271, 260, 256, 304W. NH PO=251, 239, 219, 212, 247W. HN PO=259, 258, 257, 250, 294. HH PO=238, 215, 212, 205, 245). There was no significant difference in initial PO. Discussion: Despite manipulating the pre-exercise template, PO is not reduced until physiological feedback occurs within the time trial. In this study physiological feedback modifications were evident after ~1.0 km with significant adjustments in PO based on the FiO2. It is essential for the athlete to prepare an effective pacing strategy and constantly be interpreting and responding to environmental and internal cues (Mauger et al., 2011; Tucker et al., 2009). Apparently, with changes in FiO2 subjects cannot distinguish this change, even if a low FiO2 is presented during warm-up, until physiological feedback mechanisms have time to act during the time trial. Since initial PO was not significantly different, changes in pacing strategy occurred only after afferent feedback was received.